2016
DOI: 10.1111/jpn.12439
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute lipopolysaccharide challenge on dairy goat liver metabolism assessed with 1HNMR metabonomics

Abstract: We investigated the mechanisms mediating hepatic metabolic responses to an acute lipopolysaccharide (LPS) challenge in goats. Guanzhong dairy goats (15) were randomly divided into three groups: control (CTL, saline, 0.2 ml/kg BW), lower dose LPS (LPS-L, 20 μg/kg BW) and higher dose LPS (LPS-H, 40 μg/kg BW). All injections were administered intraperitoneally twice with a 24-h interval. Forty-eight hours after the first injection, blood samples were collected to extract plasma for biochemical analysis, and liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The study, demonstrated the potential of this approach to help create a more systematic metabolome analysis16. Other recent studies in farm animals confirm the potential of NMR technique to metabolomics approaches17181920.…”
mentioning
confidence: 53%
“…The study, demonstrated the potential of this approach to help create a more systematic metabolome analysis16. Other recent studies in farm animals confirm the potential of NMR technique to metabolomics approaches17181920.…”
mentioning
confidence: 53%
“…As mentioned previously, increased circulating TG likely represents a strategy to promote LPS detoxification, as lipoproteins can help efficiently detoxify LPS. In ruminants, LPS-induced changes in TG concentrations are poorly described, as both increased (Ballou et al, 2008;Graugnard et al, 2013) and decreased (Wang et al, 2017) levels have been reported. Discrepancies in the response may be explained by sampling time, as the increase in TG appears to be short lived (Ballou et al, 2008;Graugnard et al, 2013).…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to identify serum metabolites associated with the pathogenesis and the protection against stress in broilers. Previous studies demonstrated LPS challenge caused alterations in lipid and protein metabolism in different animals ( Wan et al, 2017 ; Wang et al, 2017 ; Chirivi et al, 2022 ). In present study, taurolithocholic acid, myristoleic acid, stearoylcarnitine, PC (16:0/16:0), 1-Hexadecyl-sn-glycero-3-phosphocholine and Ser-Arg were significantly altered, suggesting that the abnormal degradation of lipid and protein were involved in the pathogenesis of stress in chicks ( Ozawa et al, 2020 ; Heidenreich et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%